2011
DOI: 10.1002/htj.20354
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement for combined convection flow of nanofluids in a vertical rectangular duct considering radiation effects

Abstract: In this paper, combined convective heat transfer and nanofluids flow characteristics in a vertical rectangular duct are numerically investigated. This investigation covers Rayleigh numbers in the range of 2 × 10 6 ≤ Ra ≤ 2 × 10 7 and Reynolds numbers in the range of 200 ≤ Re ≤ 1000. Pure water and five different types of nanofluids such as Ag, Au, CuO, diamond, and SiO 2 with a volume fraction range of 0.5% ≤ ϕ ≤ 3% are used. The three-dimensional steady, laminar flow, and heat transfer governing equations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A comprehensive study on nanofluid heat transfer characteristics and their applications can be found in Chitra and Sendhilnathan [1], Godson and colleagues [2], and Sarkar [3]. Many investigations [4][5][6][7] explained that nanofluids clearly exhibit enhanced thermal conductivity, which augments with an increase in the volumetric fraction of nanoparticles. Hwang and colleagues [8] from their research observed that heat transfer coefficient of a nanofluid decreases with an increase in the size of nanoparticles, in a natural convection case in a rectangular cavity using Al 2 0 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study on nanofluid heat transfer characteristics and their applications can be found in Chitra and Sendhilnathan [1], Godson and colleagues [2], and Sarkar [3]. Many investigations [4][5][6][7] explained that nanofluids clearly exhibit enhanced thermal conductivity, which augments with an increase in the volumetric fraction of nanoparticles. Hwang and colleagues [8] from their research observed that heat transfer coefficient of a nanofluid decreases with an increase in the size of nanoparticles, in a natural convection case in a rectangular cavity using Al 2 0 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%